Fostering Entrepreneurial Agriculture in Tanzania - Kyaruzi, Imani Silver (Dar es Salaam Mkuki na Nyota, 2011)
Fostering Entrepreneurial Agriculture in Tanzania investigates the roles of innovative farming and agriculture in Tanzania's agrarian economy. While the recent wave of global economic revolutions have transformed the agricultural and farming industries, Tanzania's economy is still in transition. The transformation toward innovative agriculture is often mentioned but the impact of such changes and the resulting opportunities have rarely been empirically tested. Entrepreneurial agriculture and local economic growth; Marketing systems and cess collection; Farmers' awareness on rural development approaches; Economic impacts of HIV and AIDS-mechanism and challenges facing the Agricultural sector; The potential of agribusiness incubators; Paradigm shift in the Tanzanian economy.
Keywords: Entrepreneurial Agriculture, Tanzanian Economy